IMPLEMENTASI KEGIATAN COOKING CLASS DALAM MENUMBUHKAN KEBIASAAN MAKAN SEHAT DI PAUD SEROJA - Ulfah; Maulida Nur; Havid Surya (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
Instilling healthy eating habits from an early age is a fundamental foundation for shaping a child’s lifelong healthy lifestyle. This study aims to describe the implementation of cooking classes in fostering healthy eating habits at PAUD Seroja, Serang City, with a particular focus on the teacher’s role in planning, delivering, and guiding the activities. A descriptive qualitative approach was employed, utilizing observation, in-depth interviews, and documentation, with participants consisting of three teachers and children involved in the program. The findings reveal that teachers play a pivotal role in systematically designing activities, selecting nutritious and easy-to-prepare menus, and guiding children through each cooking stage in a participatory manner while ensuring safety. The activity not only enhances children’s motor and social skills but also fosters their interest and awareness toward healthy food. Thus, cooking classes serve as an effective and engaging learning strategy to instill healthy eating habits from an early age.